2018
DOI: 10.1039/c8ta06471g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen/oxygen co-doped monolithic carbon electrodes derived from melamine foam for high-performance supercapacitors

Abstract: A novel nitrogen/oxygen co-doped carbon sponge (NOCS) is directly applied as a monolithic binder-free electrode for supercapacitors. It exhibits a high specific capacitance and excellent electrochemical cyclability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(104 citation statements)
references
References 49 publications
2
102
0
Order By: Relevance
“…In the XPS survey scan of MnO 2 @N–AC (Figure a), four peaks were revealed corresponding to carbon (C1s), oxygen (O1s), nitrogen (N1s), and manganese (Mn2p 1/2 and Mn2p 3/2 ). The high‐resolution C1s XPS spectrum of MnO 2 @N–AC (Figure b) showed the peaks at 288.1 eV (OCO, CO), 286.2 eV (CN, CO), and 284.5 eV (CC, CC) . Further, the N1s spectrum was analyzed to confirm the binding of nitrogen in MnO 2 @N–AC (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the XPS survey scan of MnO 2 @N–AC (Figure a), four peaks were revealed corresponding to carbon (C1s), oxygen (O1s), nitrogen (N1s), and manganese (Mn2p 1/2 and Mn2p 3/2 ). The high‐resolution C1s XPS spectrum of MnO 2 @N–AC (Figure b) showed the peaks at 288.1 eV (OCO, CO), 286.2 eV (CN, CO), and 284.5 eV (CC, CC) . Further, the N1s spectrum was analyzed to confirm the binding of nitrogen in MnO 2 @N–AC (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al reported bilayer N‐doped carbon prepared by furfuryl alcohol‐draped MS for supercapacitors, which showed the capacitance of 184 F g −1 at 5 mV s −1 scanning rate . Zhang et al N/O codoped the carbon monolithic electrode prepared from MS that exhibited a high capacitance 325 F g −1 at 10 mV s −1 scan rate and 242 F g −1 at 0.5 A g −1 current density . Wang et al developed, N‐doped AC sheets using melamine for supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%
“…The CNF capacitors all showed an ultralong cycling lifespan, and CNF-5 still had a capacitance retention of 93.6 % after 10,000 cycles. [42] In order to further understand the effect of reactive nitrogen and pore engineering on the pseudo-capacitance of EDLC and total capacitance, the Trasatti method is used to analyze and calculate the contributions of EDLC and pseudo-capacitance to the total specific capacitance of CNF-1/3/5 (10-200 mV s À 1 ). As shown in the inset, the solution resistance (R s ) is obtained from the left intercept of the real axis (Z'), and the charge transfer resistance (R ct ) is determined by the semicircle diameter.…”
Section: Two-electrode Configurationmentioning
confidence: 99%
“…More importantly, CNF-5 with 4.26 Wh kg À 1 (3.0 kW kg À 1 ) is better than some previously reported samples such as NOCS-1/10 (having 3.14 Wh kg À 1 at 3.0 kW kg À 1 ). [42] In order to further understand the effect of reactive nitrogen and pore engineering on the pseudo-capacitance of EDLC and total capacitance, the Trasatti method is used to analyze and calculate the contributions of EDLC and pseudo-capacitance to the total specific capacitance of CNF-1/3/5 (10-200 mV s À 1 ). [43] In Figure 5g-i, the EDLC of the three samples dominates their respective specific capacitances, well in line with the fact that the porous structure can increase EDLC, and is consistent with the structure in the previously analyzed PSD curve.…”
Section: Two-electrode Configurationmentioning
confidence: 99%
“…Nowadays, there are numerous nitrogen-containing 3D organic polymer such as polyurethane sponge, melamine sponge etc., [8,22,23] which can be selected as precursors for the synthesis of interconnected 3D carbon materials employing a facile pyrolysis method with nitrogen-doped simultaneously. [24,25] These polymeric sponges show great superiority for their commercially available, robust and inexpensive character. [26,27] A thermal annealing treatment in nitrogen atmosphere, one can obtain free-standing and in situ nitrogen-doped carbon monolith with large internal void space which can accommodate certain fine substances to introduce functional spices.…”
Section: Introductionmentioning
confidence: 99%